Grey Relational Analysis-Based Fault Prediction for Watercraft Equipment - Feng, Shasha; Chen, Zijian; Guan, Qunsheng; Yue, Jingtao; Xia, Chengyi (Frontiers in Physics, 2022)
In this study, we aim to investigate the fault prediction for watercraft equipment by using grey relational analysis. At first, the healthy degree model of watercraft equipment is proposed, and then two main theorems are derived to determine the health condition criteria for equipment. Lastly, the relevant simulation results are provided to verify the validity and accuracy of the healthy degree model. Current results can be helpful to effectively design the supporting mode of watercraft equipment and realize the transformation of watercraft equipment support from planned maintenance to predictive maintenance.